2022
DOI: 10.1002/lio2.771
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of circLPAR3 inhibits tumor progression and glycolysis by liberating miR‐144‐3p and upregulating LPCAT1 in oral squamous cell carcinoma

Abstract: Background: Increasing evidence demonstrated the important roles of circular RNAs (circRNAs) in human cancer progression, including oral squamous cell carcinoma (OSCC). The study intentions were to explore the role and molecular mechanism of hsa_circ_0004390 (circLPAR3) in OSCC progression.Methods: Expression of circLPAR3 in collected samples and cultured cell lines was detected with real-time quantitative reverse transcription-polymerase chain reaction (RT-qPCR). Loss-of-function experiments were performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Two studies showed that circLPAR3 expression was higher in oral squamous cell carcinoma (OSCC) samples and cells. Knockdown of circLPAR3 caused suppression of proliferation, stemness and metastasis, and induction of cell apoptosis ( Fu et al, 2022a ; Su et al, 2022 ). Mechanistically, circLPAR3 absorbed miR-643 to upregulate the expression of HMGB2.…”
Section: Role Of Circrnas In Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Two studies showed that circLPAR3 expression was higher in oral squamous cell carcinoma (OSCC) samples and cells. Knockdown of circLPAR3 caused suppression of proliferation, stemness and metastasis, and induction of cell apoptosis ( Fu et al, 2022a ; Su et al, 2022 ). Mechanistically, circLPAR3 absorbed miR-643 to upregulate the expression of HMGB2.…”
Section: Role Of Circrnas In Drug Resistancementioning
confidence: 99%
“…Su et al found that depletion of circLPAR3 reduced glycolysis and repressed tumor progression via suppression of miR-144-3p and promotion of LPCAT1 in OSCC. OSCC patients with higher expression of circLPAR3 displayed a shorter survival ( Su et al, 2022 ).…”
Section: Role Of Circrnas In Drug Resistancementioning
confidence: 99%